2009
DOI: 10.1007/s00406-009-0017-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression of NMDA receptor subunits in the cerebellum of elderly patients with schizophrenia

Abstract: To determine if NMDA receptor alterations are present in the cerebellum in schizophrenia, we measured NMDA receptor binding and gene expression of the NMDA receptor subunits in a post-mortem study of elderly patients with schizophrenia and non-affected subjects. Furthermore, we assessed influence of genetic variation in the candidate gene neuregulin-1 (NRG1) on the expression of the NMDA receptor in an exploratory study. Post-mortem samples from the cerebellar cortex of ten schizophrenic patients were compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
2
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 63 publications
1
36
2
1
Order By: Relevance
“…Adding further complications to the regional specificity of NRG1 signalling, NR2C mRNA expression has been found to be decreased in a population of schizophrenia patients with a NRG1 polymorphism in the cerebellar molecular layer of the right hemisphere and vermis (Schmitt et al, 2010). Supporting this finding, the NRG1-β isoform has been shown to upregulate the expression of NR2C mRNA in cultured cerebellar slices (Ozaki et al, 1997).…”
Section: Nr2 and Nrg1 Interactionsmentioning
confidence: 87%
“…Adding further complications to the regional specificity of NRG1 signalling, NR2C mRNA expression has been found to be decreased in a population of schizophrenia patients with a NRG1 polymorphism in the cerebellar molecular layer of the right hemisphere and vermis (Schmitt et al, 2010). Supporting this finding, the NRG1-β isoform has been shown to upregulate the expression of NR2C mRNA in cultured cerebellar slices (Ozaki et al, 1997).…”
Section: Nr2 and Nrg1 Interactionsmentioning
confidence: 87%
“…We have reported that individuals carrying at least one C allele of the NRG1 SNP rs35753505 (SNP8NRG221533) showed decreased expression of the GRIN2C (NR2C) subunit of the NMDA receptor in the right cerebellum, compared to individuals homozygous for the T allele. These results suggest that this SNP contributes to a glutamatergic hypofunction (Schmitt et al 2010). This variant forms part of the previously reported risk haplotype for schizophrenia, and has been described as a tagging SNP of the core at-risk haplotype (Stefansson et al 2002).…”
Section: Introductionmentioning
confidence: 93%
“…For each patient the history of antipsychotic treatment was assessed by examining the medical charts. Subjects ' last dose as well as the cumulative dose during the last 10 years of antipsychotic medication was calculated in chlorpromazine equivalents (CPE) according to Schmitt et al (2010). In all cases autopsy consent had been obtained from either the donor himself or a family member.…”
Section: Introductionmentioning
confidence: 99%
“…Schließlich konnte in Post-mortem-Untersuchungen des Hippocampus bei Patienten mit einer Schizophrenie eine Reduktion der mRNALevel für den NMDAR-Rezeptor 1 nachgewiesen werden [41,42]. Im Cerebellum, das eine wichtige Rolle bei kognitiven Defiziten schizophrener Patienten spielt [43], wurde neben einer verän-derten Genexpression der NMDA-Rezeptor-Untereinheit NR2 D und funktionell bedeutender Glutamattransporter bei schizophrenen Patienten ein Zusammenhang zwischen der Expression der NR2C-Untereinheit und einem Risikogen für Schizophrenie, dem Neuregulin 1, (NRG1) gezeigt [44,45]. In mehreren Arbeiten wurde repliziert, dass Patienten mit einer Schizophrenie vermehrt Risikopolymorphismen bestimmter Gentranskripte (z.…”
unclassified